2014
DOI: 10.1590/s1677-5538.ibju.2014.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tissue Factor Expression is an Independent Predictor of Mortality in Clear Cell Carcinoma of the Kidney

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: Increased expression of tissue factor (TF), a primary initiator of the extrinsic coagulation pathway, has been associated with a worse prognosis in a variety of solid tumors. We report for the first time the correlation of the immunohistochemical expression of tissue factor with clinical and pathological outcomes in clear cell carcinomas of the kidney. Materials and Methods: immunohistochemical expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
7
0
5
Order By: Relevance
“…In the samples of patients with Wilms tumors, an increased TF expression was an independent prognostic factor of overall survival (HR 5.6; p<0.01) ( 20 ). In samples of patients with clear cell RCC an increased expression of TF was also an independent predictor of overall survival (HR 4.03; p=0.03) ( 21 ). Förster et al have previously studied TF both in tissue and in serum of patients with RCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the samples of patients with Wilms tumors, an increased TF expression was an independent prognostic factor of overall survival (HR 5.6; p<0.01) ( 20 ). In samples of patients with clear cell RCC an increased expression of TF was also an independent predictor of overall survival (HR 4.03; p=0.03) ( 21 ). Förster et al have previously studied TF both in tissue and in serum of patients with RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Serum TF levels were tested as possible tumor markers in ovarian and pancreatic cancers, with promising results ( 18 , 19 ). We have previously reported that an increased immunohistochemical expression of TF in Wilms tumors ( 20 ) and in clear cell RCC ( 21 ) was an adverse prognostic factor, correlated with decreased overall and cancer-specific survival. The present study aims to determine whether serum levels of TF are useful as biomarkers in clear cell RCC.…”
Section: Introductionmentioning
confidence: 99%
“…При онкологических заболеваниях экспрессия TF изменяется по сравнению с его экспрессией в здоровом организме. Клетки множества типов злокачественных новообразований содержат значительное количество TF, что было показано с помощью иммуногистологического анализа образцов злокачественных тканей пациентов [2,12,[49][50][51][52], иммунохимического анализа клеточных культур [53] и анализа полимеразной цепной реакции (ПЦР) мРНК TF в опухолевых клетках различных типов [50,[52][53][54].…”
Section: локализация тканевого фактора при онкологических заболеванияхunclassified
“…Опухоли мочеполовой системы светлоклеточный рак почки Экспрессия tf. Для светлоклеточного рака почки [2] высокая экспрессия TF характерна для III и IV стадий по TNM-классификации, низкая -для I и II стадий.…”
Section: фундаментальные исследования в практической медицине на соврunclassified
See 1 more Smart Citation